(untitled) (Journal of the College of Languages (JCL), 2022)
Deception is an inseparable facet of political discourse in attaining strategic political gains though compromising public opinion. However, the employment of discursive deception strategies by the policy-making institutions of think tanks has not received due attention in the literature. The current study aims at exploring how the ideologizing deception strategies are utilized by the conservative American think tank of the Washington Institute to reproduce socio-political realities and re-shape public opinion. To fulfill this task, van Dijk’s (2000) notion of ideological polarization which shows positive self-representation and negative other representation is adopted to conduct a critical discourse analysis of four Arabic texts released with the main focus on four different political topics. Results reveal the centrality of employing deception strategies for the sake of realizing political wins for establishing an ideological hegemony while simultaneously polarizing an Us against Them extreme.